Late‐Onset Tay‐Sachs Disease in an Irish Family. Issue 1 (28th October 2020) - Lefter, Stela; O' Mahony, Olivia; Sweeney, Brian; Ryan, Aisling M.
ABSTRACT: Background: Late‐onset Tay‐Sachs disease (LOTS) is an autosomal‐recessive lysosomal storage disease caused by deficient β‐hexosaminidase A activity. LOTS is rare in the Ashkenazi Jews, but even rarer in the non‐Jewish population. Cases: We report an Irish family expanding the LOTS phenotype (ataxia, diffuse muscle wasting, dystonia, chorea, belly dancer's dyskinesia, and neuropsychiatric features) associated with the known HEXA variant 1073 + 1G > A and a novel variant c.459 + 24G > C. Conclusions: LOTS should be considered in patients with similar symptoms and cerebellar atrophy on brain imaging. Abstract : View Supplementary Video 1 View Supplementary Video 2 View Supplementary Video 3